Effective control of Listeria innocua by combination of nisin, pH and low temperature in liquid cheese whey - Gallo, Luciana Ines (2007)
The effect and interactions of pH (5.5, 6.0 and 6.5), temperature (7 C and 20 C) and nisin (100 IU/ml; 300 IU/ml), on the growth and survival of Listeria innocua in liquid cheese whey (LCW) were studied. Growth data were analyzed by non-linear regression analysis to generate ‘‘best fit’’ Gompertz and logistic models. The growth kinetics of L. innocua was dependent on the interaction of the three variables, particularly on the lag phase duration. The effectiveness of nisin in controlling the growth of L. innocua in LCW was more pronounced at 7 C than at 20 C and as the pH decreased from 6.5 to 5.5. As a consequence, this combined treatment may provide LCW with a degree of protection against this microorganism, particularly if employed in conjunction with low temperature